2018
DOI: 10.1371/journal.ppat.1007042
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic characterization of CSF B cells in virus-associated neuroinflammatory diseases

Abstract: Intrathecal antibody synthesis is a well-documented phenomenon in infectious neurological diseases as well as in demyelinating diseases, but little is known about the role of B cells in the central nervous systems. We examined B cell and T cell immunophenotypes in CSF of patients with HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) compared to healthy normal donors and subjects with the other chronic virus infection and/or neuroinflammatory diseases including HIV infection, multiple scleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 65 publications
0
43
0
1
Order By: Relevance
“…Although CD4+/CD25+ Tregs can be infected by HTLV-1 and HAM/TSP patients have been shown to have a high number of CD4+/CD25+ Tregs with impaired function and higher HBZ mRNA levels (Araya et al, 2011; Enose-Akahata et al, 2018), the results presented here indicate that in HAM/TSP patients, HBZ protein can be detected in CD4+ T cells not displaying the classical phenotype of Treg cells. Thus, the possible uncoupling of HBZ mRNA and protein expression in CD4+CD25+ Tregs as well as in other CD4+ T cell subpopulations in both AC and HAM/TSP patients (Yamano et al, 2009; Leal et al, 2013; Araya et al, 2014; Billman et al, 2017) certainly requires further investigation.…”
Section: Discussionmentioning
confidence: 52%
“…Although CD4+/CD25+ Tregs can be infected by HTLV-1 and HAM/TSP patients have been shown to have a high number of CD4+/CD25+ Tregs with impaired function and higher HBZ mRNA levels (Araya et al, 2011; Enose-Akahata et al, 2018), the results presented here indicate that in HAM/TSP patients, HBZ protein can be detected in CD4+ T cells not displaying the classical phenotype of Treg cells. Thus, the possible uncoupling of HBZ mRNA and protein expression in CD4+CD25+ Tregs as well as in other CD4+ T cell subpopulations in both AC and HAM/TSP patients (Yamano et al, 2009; Leal et al, 2013; Araya et al, 2014; Billman et al, 2017) certainly requires further investigation.…”
Section: Discussionmentioning
confidence: 52%
“…The ability of cross-reactive autoantibodies to access the CSF and brain is a critical effector component to the pathogenesis of autoimmune encephalitis. There is increasing evidence that the components of the peripheral immune system are able to cross the BBB and enter the central nervous system (CNS) (52,(56)(57)(58)(59)(60) when permeability of the BBB is compromised by infectious or non-infectious factors (57,58). Bacteria, including group A streptococci, can impair BBB function in neurological niches like the olfactory bulb leading to loss of function, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of certain adhesion molecules such as VCAM-1, ICAM-1, and ICAM-2 on CNS vessels during inflammation can promote the trafficking of lymphocytes into the CNS. Antibody-secreting B cells are found in the brain and CSF in infectious neurological diseases as well as in demyelinating diseases ( 59 ). One study suggested short-term sleep deprivation led to an influx of B cells across the BBB through a mechanism involving CXCR5 ( 60 ), a chemokine linked to BBB permeability ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent analysis reported that the presence of hnRNPA1-specific antibodies in the CSF was not specific to this disease (Yukitake et al., 2008). Recent analysis shows intrathecal HTLV-1 specific antibody is significantly elevated in HAM/TSP patients compared to ACs, which is significantly correlated with antibody secreting B cells (ASCs) (Enose-Akahata et al., 2018). These results suggest that elevated ASCs may contribute to antibody production in the CSF and importance of the B cell compartment in the pathogenesis of developing of HAM/TSP.…”
Section: Host Immune Responese To Htlv-1mentioning
confidence: 99%